การสอนโดยใช้โครงงานเรื่องปรัชญาเศรษฐกิจพอเพียง เพื่อพัฒนาความสามารถในการใช้ภาษาอังกฤษของนักเรียนชั้นมัธยมศึกษาปีที่ 6 - พันธุ์ชัยเพชร, สมทวี; จอกทอง, เฉลิมศรี (Ratchaphruek Journal, 2016)
การสอนภาษาอังกฤษโดยใช้โครงงานเรื่องปรัชญาเศรษฐกิจพอเพียงเป็นการสอนโดยใช้กระบวนการกิจกรรมโครงงานและหลักปรัชญาเศรษฐกิจพอพียงเพื่อเพิ่มความสามารถ ด้านภาษาอังกฤษให้แก่นักเรียน วัตถุประสงค์ของการวิจัยนี้เพื่อศึกษาผลการสอนภาษาอังกฤษ โดยใช้โครงงานเรื่องปรัชญาเศรษฐกิจพอเพียงที่มีต่อความสามารถด้านภาษาอังกฤษของนักเรียน และเพื่อศึกษาทัศนคติของนักเรียนที่มีต่อการเรียนภาษาอังกฤษด้วยโครงงานเรื่องปรัชญาเศรษฐกิจพอเพียง กลุ่มตัวอย่างคือนักเรียน จำนวน 35 คน ที่กำลังเรียนอยู่ในชั้นมัธยมศึกษาปีที่ 6 ปีการศึกษา 2556 โรงเรียนบุญเหลือวิทยานุสรณ์ จังหวัดนครราชสีมา เขตพื้นที่การศึกษามัธยมศึกษา เขต 31 กลุ่มตัวอย่างได้จากการสุ่มตัวอย่าง โดยการแบ่งกลุ่ม เครื่องมือที่ใช้ในการวิจัยได้แก่ แผนการจัดการเรียนรู้แบบโครงงาน 5 ขั้นจำนวน 7 แผน แบบทดสอบความสามารถด้านภาษาอังกฤษ และแบบสอบถามความคิดเห็นของนักเรียนหลังการเรียนรู้ด้วยโครงงานเรื่องปรัชญาเศรษฐกิจพอเพียง สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย ค่าส่วนเบี่ยงเบนมาตรฐาน และการทดสอบค่าที (t-test) ผลการศึกษา พบว่า 1) ค่าเฉลี่ยของคะแนนจากแบบทดสอบความสามารถทางภาษาอังกฤษของนักเรียนหลังเรียนเพิ่มขึ้นอย่างมีนัยสำคัญ และ 2) นักเรียนมีทัศนคติที่ดีต่อการเรียนรู้ภาษาอังกฤษด้วยโครงงานเรื่องปรัชญาเศรษฐกิจพอเพียง นอกจากนี้นักเรียนได้ใช้แหล่งข้อมูลจริงในการทำโครงงานและประเมินผลงาน นักเรียนมีความเห็นว่าการเรียนรู้ด้วยโครงงานส่งเสริมการเรียนรู้ร่วมกัน The Use of Project Work on Sufficiency Economy Philosophy to Enhance English Proficiency of Grade 12 Students Teaching English by using project work on Sufficiency Economy Philosophy is the integration of English project work and the principles of Sufficiency Economy Philosophy to enhance students’ English proficiency. The purposes of this research were to find out the effects of teaching English through project work on Sufficiency Economy Philosophy on the students’ English proficiency and to study the students’ opinion towards the use of this strategy. The samples were 35 grade-12 students in the second semester of the 2013 academic year at Bunlua Withayanusorn School, Nakhon Ratchasima, Secondary Educational Service Area Office 31. They were selected using cluster random sampling. The research instruments consisted of 7 lesson plans to teach the students following 5 stages of project procedures, the English proficiency test to assess students’ English ability, and a questionnaire to explore students’ opinion after learning English through project work. The statistics used were the mean score, standard deviation and t-test for dependent. The findings were as follows: 1) the post-test mean score of the English proficiency test of the students learning English through project work on Sufficiency Economy Philosophy was significantly improved, and 2) the students had positive opinion towards learning English through project work on Sufficiency Economy Philosophy. In addition, project work provided them with opportunity to use real information sources, to process information and to evaluate the information gained. They also agreed that the learning process of project work promoted cooperation among group members and working in team.